Democratic practices in Indonesia: youth political participation and the transformation of protest communication in the digital era - Ach Fawaidi (Universitas Negeri Yogyakarta, 2025)
This study examines the practice of democracy learning in Indonesia by emphasizing the importance of citizen involvement in democratic processes, particularly through public demonstrations. A qualitative approach was employed, utilizing semi-structured interviews, observations, and a comprehensive literature review as data collection methods. The data were derived from reports on public protests in both print and online media, as well as expert interviews relevant to the issue. The findings indicate a notable shift in the patterns of youth participation in political engagement. In addition to conventional forms of protest, such as physical demonstrations, contemporary participation has increasingly expanded into digital spaces, where efforts to amplify issues through social media virality play a crucial role in mobilizing public support. Furthermore, the study identifies a transformation in the language and style of protest among Indonesian youth compared to those observed during the Reform Era. These demonstrations reflect a rational expression of citizens’ concerns toward national issues, representing an important dimension of civic competence in a democratic society.